Potential Clinical Uses of CDK Inhibitors: Lessons from Synthetic Lethality Screens - Vymětalová, Ladislava; Kryštof, Vladimír (Medicinal research reviews, 2015)
Developments in genetic and genomic technology have produced vast quantities of data that are gradually yielding new insights into fundamental cellular and molecular processes. In particular, they have revealed some differences between normal and transformed cells that could potentially be exploited to develop targeted, personalized cancer therapies with unprecedented efficiencies. This review summarizes recent findings from synthetic lethality (SL) screens against cyclin-dependent kinases (CDKs) that can be targeted with small molecule kinase inhibitors. SL screens can be used to identify cancers sensitive to CDK inhibitors. Several SL partners of specific CDKs have been identified, including MYC, K-Ras, VHL, PI3K, and PARP, all of which are discussed in the review. CDK inhibitors have been in clinical trials for nearly 20 years and it has become clear that effective therapy using these compounds will require careful selection of patients with respect to the specific molecular phenotype of their disease.
Keywords: cyklin-dependentní kinasy; Cyclin-Dependent Kinases; protinádorové látky; synthetic lethality; Antineoplastic Agents; Protein Kinase Inhibitors; inhibitor; Humans; cancer; drug; inhibitory proteinkinas; lidé; cyclin-dependent kinase